2022
DOI: 10.1111/tpj.15895
|View full text |Cite
|
Sign up to set email alerts
|

THIAMIN REQUIRING2 is involved in thiamin diphosphate biosynthesis and homeostasis

Abstract: SUMMARY The THIAMIN REQUIRING2 (TH2) protein comprising a mitochondrial targeting peptide followed by a transcription enhancement A and a haloacid dehalogenase domain is a thiamin monophosphate (TMP) phosphatase in the vitamin B1 biosynthetic pathway. The Arabidopsis th2‐3 T‐DNA insertion mutant was chlorotic and deficient in thiamin diphosphate (TDP). Complementation assays confirmed that haloacid dehalogenase domain alone was sufficient to rescue the th2‐3 mutant. In pTH2:TH2‐GFP/th2‐3 complemented plants, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…Besides thiamin, thiamin monophosphate (TMP) and thiamin diphosphate (TDP) are the two other major forms of vitamers among the six currently known thiamin vitamers (Fitzpatrick & Chapman, 2020). Although TDP is considered to be the bioactive form, the possibility that thiamin and TMP also have biological functions can not yet be excluded (Hsieh et al., 2022). The pathways that plants use to synthesize B1 vitamers are distributed among plastids, cytosol, and mitochondria (Hsieh et al., 2022; Joshi et al., 2021; Mimura et al., 2016).…”
Section: Vitamin Coenzymes: Physiological Developmental and Metabolic...mentioning
confidence: 99%
See 3 more Smart Citations
“…Besides thiamin, thiamin monophosphate (TMP) and thiamin diphosphate (TDP) are the two other major forms of vitamers among the six currently known thiamin vitamers (Fitzpatrick & Chapman, 2020). Although TDP is considered to be the bioactive form, the possibility that thiamin and TMP also have biological functions can not yet be excluded (Hsieh et al., 2022). The pathways that plants use to synthesize B1 vitamers are distributed among plastids, cytosol, and mitochondria (Hsieh et al., 2022; Joshi et al., 2021; Mimura et al., 2016).…”
Section: Vitamin Coenzymes: Physiological Developmental and Metabolic...mentioning
confidence: 99%
“…Although TDP is considered to be the bioactive form, the possibility that thiamin and TMP also have biological functions can not yet be excluded (Hsieh et al., 2022). The pathways that plants use to synthesize B1 vitamers are distributed among plastids, cytosol, and mitochondria (Hsieh et al., 2022; Joshi et al., 2021; Mimura et al., 2016). Because other studies have yielded in‐depth descriptions of thiamin biosynthesis pathways in different organisms (Hsieh et al., 2022), we will only briefly describe the general aspects of thiamin biosynthesis in plants.…”
Section: Vitamin Coenzymes: Physiological Developmental and Metabolic...mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, TMP is dephosphorylated to thiamin, which is then pyrophosphorylated to form TDP in plants (Figure 1a). Arabidopsis th2 mutants impaired in TMP phosphatase have reduced thiamin and TDP levels and a chlorotic phenotype (Hsieh et al, 2017(Hsieh et al, , 2022Mimura et al, 2016). We previously showed that feeding thiamin could rescue the th2 mutants (Hsieh et al, 2017(Hsieh et al, , 2022.…”
Section: E Coli Thil Rescues the Arabidopsis Th2-3 Mutantmentioning
confidence: 99%